Study on Enhanced Oil Recovery with Viscoelastic Self-regulator - Zhou, Xing (International Journal of Natural Resources and Environmental Studies, 2024)
After long-term water flooding in low permeability reservoirs, dominant channels develop, and viscoelastic self-regulating agents can block large pores and inhibit bottom water coning. Based on the physical model experiment of sand filling pipe and the dynamic simulation system of pressure conduction online detection, this paper simulates the displacement characteristics of low permeability reservoir, and quantitatively studies the regulation and displacement performance of high permeability fracture model and low permeability matrix model of sand filling pipe with viscoelastic self-regulator under different permeability difference and different injection speed. Through pressure gradient, diversion rate and recovery factor, the formation energy conduction law under different injection and production systems is revealed. The results show that when the permeability difference is small, the blocking position of the regulating and flooding agent is in the front of the middle of the low permeability pipe and in the back of the middle of the high permeability pipe, and the opposite is true when the permeability difference is large, and the pressure gradient of the large permeability difference is greater than that of the small permeability difference. With the increase of flow rate, the pressure gradient increases gradually. The slug also increases, and the peak of the hyperosmotic tube gradually moves toward the inlet end, and the peak of the hypoosmotic tube gradually moves toward the outlet end. The formation energy conduction efficiency is positively correlated with the injection rate, that is, the higher the injection rate is, the faster the pressure rise at the production well is.